IMPLEMENTASI PERATURAN DISPENSASI NIKAH BERDASARKAN UNDANG-UNDANG NO 16 TAHUN 2019 TENTANG PERNIKAHAN DI KECAMATAN KEMUNING KOTA PALEMBANG - Nirvananda, Della; Isabella, Isabella; Amaliatulwalidain, Amaliatulwalidain (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2023)
The research aims to find out how the implementation of marriage regulations, Marriage Law no. 16 of 2019 in Kemuning District, Palembang City. The research method used is a descriptive method with a qualitative approach. Data collection techniques used include observation, interview and documentation methods, as well as sampling techniques, namely, with individuals and groups who may have information about the subject being studied. Qualitative descriptive method was used as a research method. As data collection methods, observation, survey and documentation methods were used, as well as sampling methods, namely, people who knew the subject of investigation in Kemuning District, Palembang City. Furthermore, the results of the analysis and field results of this research use Van Metter and Van Horn's theory which includes 6 indicators, namely size and policy, resources, implementation characteristics, implementation attitude, communication between organizations, economic, social and political environment. This indicates that the government itself has not implemented it effectively. good and optimal Decree Law No. 16 of 2019 concerning Marriage in Kemuning District, Palembang City. The unfavorable social, economic and political environment causes the implementation of Law No. 16 concerning Marriage to not run smoothly and optimally. Based on the research conducted, it was found that the implementation of the marriage dispensation by the Office of Religious Affairs (KUA) in Kemuning District, Palembang City has not run well and optimally because the local government has not been optimal and the social, economic and political environment has not run well and optimally. Keywords: Implementation; Marriage; Dispensation